Distribución potencial del bagre rayado (Pseudoplatystoma magdaleniatum Buitrago-Suárez & Burr 2007) en condiciones actuales y bajo un escenario de cambio climático (2023)
The Bagre rayado (P. magdaleniatum) is an endemic species to the Magdalena basin of Colombia. This species is known to have a migratory behavior and a high commercial value in the market. Unfortunately, one of its largest threats is climate change, however, the effect of this phenomenon on the species potential distribution has not been evaluated.